GC/MS PROFILING AND EVALUATION OF ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF BAYUR (Pterospermum javanicum) BARK EXTRACT - Praptiwi, Praptiwi; Fathoni, Ahmad (LIPI Press, 2017)
This study aims to identify the chemical compounds of ethyl acetate extract of the bark of bayur (Pterospermum javanicum) and to evaluate its antibacterial activity and potential antioxidant. The estimation of total flavonoid was done by spectrophotometry method. The chemical compounds were analyzed by gas chromatography-mass spectrometry (GC-MS). The antibacterial assay against Staphylococcus aureus Ina-CC B5 and Escherichia coli Ina-CC B4 was done by TLC-bioautographic method, whereas the potential antioxidant was determined by DPPH radical scavenging assay. Meanwhile, its minimum inhibitory concentration (MIC) value and IC50 of the extract were done on microplate 96 well by serial microdilution method. GC/MS analysis revealed the presence of 31 identified chemical compounds in the extract with total flavonoid was 625 mg CE/gram extract. The MIC values against E.coli Ina-CC B5 and S. aureus Ina-CC B4 were >256 ug/ml. The IC50 from DPPH radical scavenging assay was 48.92 ppm indicating that ethyl acetate extract of the bark of bayur is potent antioxidant.